2017
DOI: 10.1155/2017/9658030
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anti‐Inflammatory Effects of Flavonoid‐Rich Common and Tartary Buckwheat Sprout Extracts in Lipopolysaccharide‐Stimulated RAW 264.7 and Peritoneal Macrophages

Abstract: Buckwheat sprouts have been widely consumed all around world due to their great abundance of bioactive compounds. In this study, the anti-inflammatory effects of flavonoid-rich common buckwheat sprout (CBS) and tartary buckwheat sprout (TBS) extracts were evaluated in lipopolysaccharide- (LPS-) stimulated RAW 264.7 murine macrophages and primary peritoneal macrophages from male BALB/c mice. Based on the reversed-phase HPLC analysis, the major flavonoids in CBS were determined to be C-glycosylflavones (orientin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…Hence, based on the results of cell proliferation and migrations, these four compounds may serve as lead in the breakthrough of therapeutic bioactive agents that may improve wound healing. Generally, these flavonoid C-glycosides were reported to possess high antioxidant [22][23][24], and anti-inflammatory activities [16,17], and may be associated with wound healing enhancement. Further studies should be conducted on the correlation of these activities and wound healing properties in OPL extracts and flavonoid enriched extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, based on the results of cell proliferation and migrations, these four compounds may serve as lead in the breakthrough of therapeutic bioactive agents that may improve wound healing. Generally, these flavonoid C-glycosides were reported to possess high antioxidant [22][23][24], and anti-inflammatory activities [16,17], and may be associated with wound healing enhancement. Further studies should be conducted on the correlation of these activities and wound healing properties in OPL extracts and flavonoid enriched extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that major compounds of KIOM-2015E identified orientin, isoorientin, and vitexin [ 23 ]. Especially, vitexin has anti-inflammatory [ 24 , 25 ], anticancer [ 26 , 27 ], and antioxidant properties [ 28 ]. Our study showed that KIOM-2015E also reduced the levels of proinflammatory factors TNF- α and IL-6 in serum.…”
Section: Discussionmentioning
confidence: 99%
“…Extraction Ethanol and methanol are the most frequently used solvents for the extraction of rutin from crops. [21] Methanol extracts were prepared according to the procedure of Nam, Lim, & Lee [22] with some modifications. Samples were accurately weighed and extracted with 80% aqueous methanol.…”
Section: Determination Of Total Flavonoid Rutin Isoquercetin and Qmentioning
confidence: 99%